Partial prostatectomy: technically feasible, but patient selection is paramount - Ball, Mark W. (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
The goal of treating localized prostate cancer is to eradicate clinically significant cancers while maximizing preservation of urinary and sexual function. Many types of ablative therapy have emerged over the past several years, with the hope of minimizing morbidity, but with variable oncologic outcomes (1). As a consequence, new therapies are continually being evaluated. Villers and colleagues recently reported on a case series of patients with low- and intermediate-risk prostate cancer than underwent anterior partial prostatectomy (APP) (2). With a median follow-up of 30 months, the authors demonstrated excellent function outcomes with 100% continence and 83% potency rates. Surgical innovation should never be disparaged, especially when performed rigorously and on protocol, and the authors should be commended for identifying a need for a focal therapy option for anterior tumors, devising a novel technique to treat it, and studying the outcomes of their therapy. On the other hand, even in the experimental setting, appropriate patient selection is critical to ensure that neither undertreatment nor overtreatment occur.